Characterization of polymer inclusion membranes (PIM) containing phosphonium ionic liquids and their application for separation of Zn(II) from Fe(III). Issue 6 (20th February 2018) - Baczyńska, Monika; Słomka, Żaneta; Rzelewska, Martyna; Waszak, Michał; Nowicki, Marek; Regel‐Rosocka, Magdalena
Abstract: BACKGROUND: Hydrometallurgical separation of Zn(II) from Fe(III) from HCl solutions is an important issue to regenerate spent effluents. Polymer inclusion membranes (PIMs) are an attractive technique for selective separation and concentration of low concentrated target metal ions, as an alternative to liquid–liquid extraction. RESULTS: PIMs containing phosphonium ionic liquids trihexyl(tetradecyl)phosphonium chloride (Cyphos IL101) or bis (2, 4, 4‐trimethylpentyl)phosphinate (Cyphos IL104), as metal ion carriers, o ‐nitrophenyloctyl ether (NPOE) as a plasticizer and triacetate cellulose (CTA) as a polymer matrix were prepared and characterized by contact angle measurements, scanning electron microscopy, atomic force microscopy and nanoindentation measurements. An important aspect was to determine the influence of PIMs ageing on their morphology and efficiency of Zn(II) transport. Finally, PIMs were applied for separation of Zn(II) from Fe(III). CONCLUSION: The surface of the IL‐containing PIMs was characterized as hydrophilic, rough, without apparent pores. However, phase contrast images indicated that the plasticized membranes were not fully homogeneous. Stability of the PIMs, particularly of those without the plasticizer or without the carrier, is affected by ageing. Finally, a membrane‐based successful separation of Zn(II) from Fe(III) was developed with 1 mol L ‐1 HCl as a stripping phase for Fe(III), while the majority of Zn(II) were retained in the feed phase ( S Fe(III)/Zn(II) = 8.85). © 2017 Society of Chemical Industry